Local thalamic atrophy associates with large-scale functional connectivity alterations of fronto-parietal cortices in genetic generalized epilepsies. Issue 1 (11th June 2019) - Boss, Nicolas; Abela, Eugenio; Weisstanner, Christian; Schindler, Kaspar; Wiest, Roland
Genetic generalized epilepsies (GGEs) are a group of seizure syndromes that start in childhood and adolescence. Although generally viewed as benign, large-scale epidemiological studies suggest that a significant proportion of GGE patients suffer from drug-resistant seizures, cognitive impairment and social problems. This motivates further research into their pathophysiology, which is still incompletely understood. GGE is characterized clinically and on the encephalogram by seizures that seem to involve both hemispheres simultaneously – hence the idea of a 'generalized' process. However, findings from experimental animal studies suggest that seizures in GGE arise due to complex functional alterations within a network that involves fronto-parietal cortex and midline thalamus. In line with these results, neuroimaging studies have found metabolic changes in midline frontal and posterior parietal cortices during GGE seizures and atrophy of both frontal lobe structures and thalamus in GGE patients. Pathology of fronto-thalamic networks seems therefore to be a core feature of GGE. It is unknown how alterations of structure and function between different sites of the network influence each other. Given that the thalamus exerts widespread influence on cortical function, we hypothesized that thalamic atrophy in GGE patients would lead to functional impairment in cortical networks. To test this hypothesis, we performed a case–control study on patients with GGE and healthy controls (HCs), using computational neuroanatomical and functional connectivity techniques. Confirming our hypothesis, we found atrophy in midline thalamic regions preferentially connected to midline (pre-) frontal cortex, and correlated functional disconnection between midline frontal and posterior parietal cortex. Of note, we found increased functional connectivity between the left-sided thalamus and the left medial prefrontal cortex, and a decrease in interhemispheric functional connectivity between bilateral parietal cortex in patients compared to HCs. Taken together, our results suggest that even highly localized subcortical structural changes might lead to large-scale network effects in GGE.